A CHASIDE Test-based Analysis for Identifying Adolescents Characteristics Impacting their Vocational Orientation: Case of private schools in the city Barranquilla, Colombia (2024)
This research is oriented to the identification of characteristics in the choice of professional careers in adolescents in eleventh grade. A total of 270 young people between the ages of 15 and 20 years old, all students at private schools in the city of Barranquilla, Colombia, were surveyed. A test called CHASIDE was used, which is focused on the occupational environment. Among the results, we found career options chosen by the students, the different inclinations in the workplaces where they plan to work, competencies in adolescents regarding the choice of career, and the identification of learning channels according to areas of knowledge. In the future, we seek to analyze whether there is a relationship between learning channels, personality, and career choice, and thus develop technological tools and algorithms for career choice, in order to address career orientation as the main axis of success in higher education